HAKIM SEBAGAI TOKOH SENTRAL DALAM PENEGAKAN HUKUM DI INDONESIA - Suhri Hanafi (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2021)
The judge's decision that is a reflection of the upholding or not of law and justice, can not be separated from the role and responsibility of judges both legally and morally as a central figure in law enforcement. This article seeks to describe the responsibility of judges in controlling law enforcement and justice processes in Indonesia by presenting data, both normative, and empirical data. Referring to the facts, the legal downturn that has occurred for decades, poses a severe challenge to the world of justice, especially internal judges in restoring the stability of law enforcement and public trust in the profession of judges. So far, the authority has made new breakthroughs in organizing law enforcement institutions including the profession of judges with integrity and have a great responsibility both legal and moral responsibility. The issuance of several regulations and the establishment of several new legal institutions are evidence of serious efforts to realize fair law enforcement, although it must be recognized that there are still many challenges and obstacles, especially for internal judges.